2015
DOI: 10.4236/ojmp.2015.42004
|View full text |Cite
|
Sign up to set email alerts
|

Body Image and Personality in Aesthetic Plastic Surgery: A Case-Control Study

Abstract: Introduction: The amount of research on the relationship between plastic surgery and psychological features, such as personality disorders and indexes of body image dissatisfaction, has increased significantly in the last years. Aim: The aim of the present study was to examine these psychological features among Italian patients who underwent aesthetic plastic surgery, testing the mediating role of the mass media influence on the relationship between them and the choice of aesthetic plastic surgery. The Persona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 43 publications
0
9
0
1
Order By: Relevance
“…Psychopathological research suggests that aesthetic rhinoplasty volunteers exhibit stronger psychopathological symptoms [11] [12]. Findings indicate that patients seeking aesthetic rhinoplasty fare worse in somatization, anxiety, depression [13], social dysfunction, depression, general health [14], and self-esteem [15] [16].…”
Section: Introductionmentioning
confidence: 99%
“…Psychopathological research suggests that aesthetic rhinoplasty volunteers exhibit stronger psychopathological symptoms [11] [12]. Findings indicate that patients seeking aesthetic rhinoplasty fare worse in somatization, anxiety, depression [13], social dysfunction, depression, general health [14], and self-esteem [15] [16].…”
Section: Introductionmentioning
confidence: 99%
“…19 Previous studies have shown that people with a negative image of their body have a higher tendency to cosmetic surgery. [19][20][21] Farshidfar et al showed that the fears and worries about physical appearance and body deformity were predictors of a tendency towards cosmetic surgery. 22 The mental image of the body is one of the major concerns for the young and teenager.…”
mentioning
confidence: 99%
“…For some authors, dissatisfaction with physical appearance or body image is believed to be one of the most important motivational factors for seeking esthetic surgery. 8 However, our research has allowed us to show that what appears to be an esthetic annoyance might in fact be a more complex psychological issue that often touches a subject’s sense of identity, and which goes far beyond a simple question of appearance. This phenomenon is part of the concept of body-screen , introduced by Mimoun.…”
Section: Discussionmentioning
confidence: 93%
“…Specifically, surgery allows patients to attain a better self satisfaction of their appearance, an improvement in body image, a higher selfesteem, and a decrease in mild depressive and anxiety symptoms, 2,5 this being observed even many years after the intervention. 3 Nevertheless, recent studies comparing cosmetic surgery patients with a control group clearly demonstrate that aesthetic surgery is sought by subjects who suffer from a body image disorder [6][7][8] or a higher level of psychopathology. 4,[9][10][11] Moreover, certain patients may be dissatisfied with their surgery, 2,3 which may trigger the onset and/or aggravation of psychiatric disorders.…”
Section: Introductionmentioning
confidence: 99%